2000
DOI: 10.1099/0022-1317-49-1-55
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic activity of the `Streptococcus milleri group' and relationship between haemolysis restricted to human red blood cells and pathogenicity in S. intermedius

Abstract: A collection of 297 clinically documented 'Streptococcus milleri' strains, identified to the genotype level by 16S rRNA gene hydridisation, was screened for haemolysis of human and animal red blood cells. Forty-nine strains (65%) of the S. intermedius genotype displayed haemolysis restricted to human blood; they were named 'exclusive human haemolytic' (EHH) S. intermedius strains. The 26 remaining S. intermedius strains were named S. intermedius non-EHH strains. Quantitative studies on the haemolysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…Among the factors that might explain the tendency for abscess formation, the cytotoxic intermedilysin has been demonstrated to be a significant contributing factor (12). Intermedilysin production is confined to the species S. intermedius, which is more frequently associated with abscess formation than S. anginosus and S. constellatus (4,7,8). However, in our study the majority of SAG isolates persisting in abscesses were identified as S. anginosus and S. constellatus.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Among the factors that might explain the tendency for abscess formation, the cytotoxic intermedilysin has been demonstrated to be a significant contributing factor (12). Intermedilysin production is confined to the species S. intermedius, which is more frequently associated with abscess formation than S. anginosus and S. constellatus (4,7,8). However, in our study the majority of SAG isolates persisting in abscesses were identified as S. anginosus and S. constellatus.…”
Section: Discussioncontrasting
confidence: 44%
“…The observation of identical or distinct AFLP types in single patients was supported by identification to the 16S rRNA ribogroup level (8,9) and by phenotypic characteristics such as the pattern of hemolysis and Lancefield group (results not shown).…”
Section: Reproducibility and Discriminatory Index By Aflp Analysismentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, S. intermedius forms more than one cluster (Fig. 3A and B) (19). The heterogeneity may be explained by recombination, which has been shown in the 16S rRNA gene for this group (38).…”
Section: Discussionmentioning
confidence: 99%
“…ILY is a member of the cholesterol-dependent cytolysins (CDC) which include streptolysin O (SLO) (4,19), and it has been shown to directly cause cell membrane damage in human erythrocytes and in cell lines derived from the major organs involved in deep-seated infections by S. intermedius (25). Therefore, ILY has been suggested as a potentially important virulence factor of this species (17,25). It has also been shown that the production level of ILY in isolates from deep-seated abscesses is 6.2-10.2-fold higher than in strains from normal habitats such as dental plaque, although no differences in production levels of other potential virulence factors such as hyaluronidase and sialidase were found (27).…”
mentioning
confidence: 99%